EDUKASI KESEHATAN DALAM MENERAPKAN HIGIENE SANITASI DAN KEAMANAN MAKANAN JAJANAN DI PASAR TRADISIONAL KOTA PADANGSIDIMPUAN - Ramadhini, Delfi; Ritonga, Nefonavratilova (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Consumption of food can be dangerous for health, because food can be a source of transmission or cause of health problems. The National Poisoning Information Center (SIKer) of the National Food and Drug Administration (2014) shows that there were 29 incidents of food poisoning in January-March 2014. A total of 5 incidents of poisoning due to consuming food snacks. Street food is food that is sold at street stalls, roadside, in public places, residential areas and other similar locations. The purpose of this PKM is to provide health education in implementing sanitation hygiene and food safety in traditional markets in Padangsidimpuan City. PKM activities are carried out using the health education method by using a checklist sheet to snack food traders at Sagumpal Bonang Market. The results of this counseling activity were continued by providing an evaluation to the hawker food vendors at Sagumpal Bonang Market, namely questions and answers about the material provided. There were a number of questions given by the extension worker to the hawker food vendors at Sagumpal Bonang Market. Based on the answers given, it shows that the hawker food vendors at Sagumpal Bonang Market understand the material provided by the extension workers. The PKM activities carried out went well. Snack food vendors at Sagumpal Bonang Market who took part in the activity seemed enthusiastic in participating in the counseling activity. The result of this activity is increasing public knowledge and educating the community about sanitation hygiene and food safety.